Rendahnya Komitmen Pemerintah dalam Penanganan Masalah Gender di Sri Lanka - Bayu Setyawan (Resolusi: Jurnal Sosial Politik, 2019)
As a developing country, Sri Lanka has problems facing other developing countries in the world. Start from the economic problems, food security and of course social and cultural. One of them is the issue of gender which has been a classic problem in Sri Lanka. The Sri Lanka people who still uphold their culture and customs are important factors for analyzing gender issues in the country. The tight culture and customs that are still held by the majority of Sri Lanka society, influence the stakeholders who should be the main spearhead of gender equality for women. Moreover, seeing the original culture which prioritizes men over women in various aspects, making women in Sri Lanka do not have the courage to do social breakdown for the freedom of women in their country. This also makes policy products (legislation) in Sri Lanka gender biased, because the perspectives of women who are actively involved in the legalization process in the country are very minimal. How exactly is public policy to cope with gender inequality in Sri Lanka? This paper seeks to explore how the policies of the Sri Lankan government towards the fulfillment of women's rights, which until now is still a social problem, is a fetter for women from their independence.